Dante’s ‘Shameless Whore’: Sexual Imagery in Anglo-American Translations of the Comedy - Crisafulli, Edoardo (TTR)

(untitled) (Association canadienne de traductologie, 2001)
AbstractThis article focuses on the strategies pursued by Anglo-American translators in dealing with Dante’s sexual imagery in the Comedy. The author attempts to explain why the original imagery — which condemns a corrupt Roman Catholic Church — has sexist connotations, and why it is reproduced in most translations in the corpus. “Fidelity” or adequacy with respect to sexual/sexist images seems striking in view of the fact that certa..n translators bowdlerize the source text or tone down the boldness of its vernacular style. It is suggested that the patriarchal nature of both the Italian and English languages explains why the use of sexist imagery is tolerated (or perhaps even encouraged) in literary texts. The findings of the analysis are then brought to bear on one important question: should the translation scholar aim to bring about “politically correct” changes in translation practice, that is, changes attenuating the offensiveness of the original language? The author advocates a descriptive approach, even though “gender and translation” seems more politicized than other areas of research within Translation Studies. The paper concludes that Translation Studies may benefit from the findings of gender studies, provided scholars in this area do not attempt to change actual translation practice and focus on the hermeneutics of translation. In fact, gender scholars can make an important contribution to Translation Studies by focusing on the ideological nature of the gendered construction of meaning.